The effect of coupling agent treatment on the mechanical and flame retardancy properties of rigid PVC-ATH nanocomposites - Samat, Noorasikin; Anuar, Hazleen; Hassan, Noor Azlina (2012)
The effects of treated nano-sized aluminum tryhidrate (ATH) inclusion on the mechanical and flame retardancy properties of rigid polyvinyl (chloride) (PVC) have been studied. PVC-ATH nanocomposites were fabricated using two-roll mills and compression moulding with different concentration of ATH, ranging from 5 – 30 phr. A silane coupling agent was used to modify the surface of nano-sized ATH particles. The results show that the incorporation of nano-sized ATH particles decreased slightly the tensile strength but improved the flexural strength and flexural modulus. Limiting oxygen index (LOI) test also showed increment in flame retardant property of PVC with the presence of nano-sized ATH particles. Nevertheless, the flame retardant of PVC reinforced with treated ATH nanoparticles was slightly lower than the untreated ATH nanoparticles. It is hypothesized that silane may interact during the burning process